A Bibliometric Analysis of Research Trends of School Library from 2015 to 2025 - Thio Helena Simarmata; Reza Fathurrahman (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this study is to analyze the research trends of school library from 2015 to 2025 using bibliometric analysis. The methodology outlines the bibliometric approach, including data collection, screening, and analysis. The publication period was set from 2005 to early 2025, covering two decades of research. This timeframe was chosen to reflect the most recent developments in school library research, aligning with significant educational policy changes, the rise of digital library integration, and evolving accreditation standards. Citation analysis identifies foundational research on the impact of school libraries on student performance, with key authors shaping the field's intellectual structure. The findings underscore the increasing importance of digital integration and interdisciplinary collaboration in school library research.